Pelatihan Keterampilan Seni Bagi Anak-Anak Paud Dan SD Di Jakarta Barat - Juniriang Zendrato (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The children in Wijaya Kusuma District had potentials in Art but they had not fully realized and developed because of the middle to lower economic and social situation. Those children also had a great desire to learn, but no one facilitated. On the other hand, their parents could not see the art potentials in children yet, so they did not encourage and appreciate children's talents in art. The purpose of this community service was to provide the arts workshop based on their respective talents and interests. The method applied was grouping the children according to their interests and talents, namely singing, drawing or crafting, and dancing. The workshop was given for two months or eight meetings. The exhibition and children's art performances were attended by parents and the surrounding community at the last meeting. The results of the activity showed the participation of children in singing, drawing or crafting activities, and dancing. The Art exhibitions presented the paintings from used paper, pencil cases from paper pulp, and dolls from eggs. The Art performances were in the form of dances and songs. The enthusiasm of parents and the community was also seen by their visits to the exhibitions and art performances.